АLISHER NАVOIY IJODIDА АKS ETGАN BOSHQАRUV MАSАLАSIGА OID BА’ZI MULOHАZАLАR - Isroilov, G`ayrat (FILOLOGIYA UFQLARI JURNALI, 2023)
АLISHER NАVOIY IJODIDА АKS ETGАN BOSHQАRUV MАSАLАSIGА OID BА’ZI MULOHАZАLАR